2014
DOI: 10.12703/p6-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal neuroprotection

Abstract: Fetal or neonatal brain injury can result in lifelong neurologic disability. The most significant risk factor for perinatal brain injury is prematurity; however, in absolute numbers, full-term infants represent the majority of affected children. Research on strategies to prevent or mitigate the impact of perinatal brain injury (“perinatal neuroprotection”) has established the mitigating roles of magnesium sulfate administration for preterm infants and therapeutic hypothermia for term infants with suspected per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 70 publications
0
23
0
4
Order By: Relevance
“…47,51,52 Although therapeutic hypothermia has improved the outlook of infants with HIE, 53,54 there remains a pressing need for neuroprotective therapies that will further reduce the high rate of neurologic disabilities. [55][56][57] We reported the safety and pharmacokinetics of high-dose Epo when given together with hypothermia. 16,17 Darbepoetin, a long-acting formulation of Epo, has also been shown to be safe in newborns undergoing hypothermia for HIE.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…47,51,52 Although therapeutic hypothermia has improved the outlook of infants with HIE, 53,54 there remains a pressing need for neuroprotective therapies that will further reduce the high rate of neurologic disabilities. [55][56][57] We reported the safety and pharmacokinetics of high-dose Epo when given together with hypothermia. 16,17 Darbepoetin, a long-acting formulation of Epo, has also been shown to be safe in newborns undergoing hypothermia for HIE.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Increased tissue concentration of TNF-α in IBD patients can lead undifferentiated M0 macrophages to polarize to M1 macrophages, classically activated macrophages [20]. M1 macrophages can also be derived from M2 in the presence of high levels of IFN-γ, a proinflammatory cytokine [21]. In contrast, M2 (alternatively activated macrophages) are induced by anti-inflammatory cytokines such as IL-10 and TGF-β [21].…”
Section: Methodsmentioning
confidence: 99%
“…M1 macrophages can also be derived from M2 in the presence of high levels of IFN-γ, a proinflammatory cytokine [21]. In contrast, M2 (alternatively activated macrophages) are induced by anti-inflammatory cytokines such as IL-10 and TGF-β [21]. The following factors were considered when obtaining a differential equation for M1 macrophage phenotype formation: concentration of tissue factors ( f 1 ) that contribute to macrophage polarization; tissue concentrations of TNF-α ( I α ) , IFN-γ ( I γ ) and TGF-β ( I β ); cytokine specific rates of macrophage activation ( σ Mα , σ Mβ , σ Mγ ) and transition between M1 and M2 phenotypes ( σ Mβ , σ Mγ ), and macrophage apoptosis (decay) rate ( μ M ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, the lifetime cost for a child born with cerebral palsy was estimated at $1.1m in the US. 7 In addition, a study that assessed the impact of preterm birth on families found that in the first year 11% had financial difficulties, 26% observed a decrease in social activities, and 28% reported that having a preterm child was emotionally challenging or difficult to accept. 8 Clearly, the prevention of preterm birth and its sequelae would have a substantial impact on both society and individuals.…”
Section: Neurodevelopmental Consequences Of Prematuritymentioning
confidence: 99%